2015
DOI: 10.5812/jjm.23411
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Genetic Association of Interleukin-16 Single Nucleotide Polymorphism (rs1131445) With Chronic Hepatitis B Virus Infection in Iranian Patients

Abstract: Background:Interleukin-16 (IL-16) is an immunomodulatory cytokine, which plays an important role in some inflammatory and autoimmune diseases such as hepatitis B, which is a major health concern worldwide.Objectives:In this study, we aimed to investigate the plausible association between IL-16 polymorphism and chronic HBV susceptibility in an Iranian population.Patients and Methods:In a case-control study, we analyzed rs1131445 polymorphism in the microRNA binding site of the IL-16 gene in 262 patients with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Many manifestations have shown that cytokines are one of the host’s most significant immunological factors, playing a crucial role in modulating the intensity and duration of the immune response (25). These soluble polypeptides also act as a defense against viral infections through driving the Th1/Th2 responses or by inhibiting viral replication (9, 11).…”
Section: Discussionmentioning
confidence: 99%
“…Many manifestations have shown that cytokines are one of the host’s most significant immunological factors, playing a crucial role in modulating the intensity and duration of the immune response (25). These soluble polypeptides also act as a defense against viral infections through driving the Th1/Th2 responses or by inhibiting viral replication (9, 11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several recent studies have paid attention to the effect of gene polymorphisms of cytokines on infectious disease outcome, response to vaccination and treatment. Polymorphisms in genes encoding cytokines may be the primary cause of clinical differences between patients; hence they can be used for the identification of individuals who are at high risk of developing hepatocellular carcinoma and chronic hepatitis (3,36). So far, we have evaluated the association of several genes with hepatitis and cancer (27,(47)(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst hepatitis viruses, hepatitis B virus (HBV), the prototype member of a family of Hepadnaviridae (1), can cause lifelong infection with a worldwide distribution and is endemic in many populations (2)(3)(4). Infection with HBV can lead to a wide range of diseases such as chronic hepatitis, acute hepatitis, asymptomatic HBV carriers, liver cirrhosis and primary hepatocellular carcinoma (HCC) (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Behelgardi et al ( 83 ) studied the influence of IL-16 T/C (rs1131445), an SNP located in a miRNA-binding site in 3′UTR of the IL-16 gene, and the risk of HBV chronic infection in an Iranian population. After adjustment for covariates, including age and gender, the TC genotype was associated with an increased risk of HBV chronic infection.…”
Section: Viral Infections and Polymorphic Variants That Affect Mirnasmentioning
confidence: 99%